2020
DOI: 10.3389/fphar.2020.01172
|View full text |Cite
|
Sign up to set email alerts
|

The Prophylactic Effect of Pinocembrin Against Doxorubicin-Induced Cardiotoxicity in an In Vitro H9c2 Cell Model

Abstract: Background The clinical use of Doxorubicin (Dox) is significantly limited by its dose-dependent cardiotoxic side effect. Accumulative evidence suggests that the use of flavonoids, such as the antioxidative Pinocembrin (Pin), could be effective in the prevention of Dox-induced cardiotoxicity. Accordingly, we investigated the ability of pinocembrin (Pin) to attenuate Dox-induced cardiotoxicity in an in vitro H9c2 cardiomyoblast model. Methodology The cardioprotective pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Therefore, increasing Doxo efficacy should go hand-in-hand with reducing side effects, expressly cardiotoxicity. In order to address the combination impact on Doxo-induced toxicity in cardiac cells, we employed embryonic rat cardiac tissue-derived H9c2 cells as a suitable in vitro model to study the anthracycline-mediated effects [39][40][41][42]. More in detail, 200 µM CGA and 0.1 µM Doxo were supplemented alone and in combination to the growing media of H9c2 and MG-63 cells for 48 h. Interestingly, whilst combination treatment further reduced the cell number and increased the percentage of PI-positive cells in MG-63 compared with Doxo alone, this trend was completely reverted in H9c2 cells (Figure 6).…”
Section: Cga Ameliorates Doxo-mediated Cytotoxicity In H9c2 Cardiomyocytesmentioning
confidence: 99%
“…Therefore, increasing Doxo efficacy should go hand-in-hand with reducing side effects, expressly cardiotoxicity. In order to address the combination impact on Doxo-induced toxicity in cardiac cells, we employed embryonic rat cardiac tissue-derived H9c2 cells as a suitable in vitro model to study the anthracycline-mediated effects [39][40][41][42]. More in detail, 200 µM CGA and 0.1 µM Doxo were supplemented alone and in combination to the growing media of H9c2 and MG-63 cells for 48 h. Interestingly, whilst combination treatment further reduced the cell number and increased the percentage of PI-positive cells in MG-63 compared with Doxo alone, this trend was completely reverted in H9c2 cells (Figure 6).…”
Section: Cga Ameliorates Doxo-mediated Cytotoxicity In H9c2 Cardiomyocytesmentioning
confidence: 99%
“…1 A) is a natural flavonoid compound, which could be extracted from honey, propolis and several other plants (Lan et al 2015 ; Rasul et al 2013 ) in addition to artificial synthesis (Costa and Leitao 2011 ), exerting anti-inflammatory, antibacterial, anti and anticancer effects (Rasul et al 2013 ; Ye et al 2019 ), along with the emphasized antioxidant effect (Kim et al 2020 ; Sangweni et al 2020 ). As previously demonstrated, the phenolic structure of Pino responsible for direct ROS elimination as well as both phenolic and nonphenolic structures that intensify the antioxidant defense (Habtemariam 2019 ) account for the antioxidant effect of Pino, by which Pino has been studied and applied in a wide variety of diseases, such as neurodegenerative diseases, atherosclerosis, doxorubicin-induced cardiomyocyte toxicity (Sangweni et al 2020 ; Sang et al 2012 ; Liu et al 2014 ). However, given that several antioxidants for myocardial infarction and HF are invalid or insufficient to convert to clinical use, whether the antioxidant effect of Pino could be fulfilled in the therapy of PIHF remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of pro-apoptotic factors such as cytochrome c enter the cytoplasm from mitochondria, activate the caspase pathway, initiate the endogenous apoptosis pathway and finally lead to cardiomyocyte death (33). Other studies also found that DOX can cause abnormal mitochondrial morphology and structure, lipid deposition and irregular arrangement of myofilaments, accompanied by myofilament breakage and dissolution (4,10). This indicates that mitochondrial function serves an important role in DOX induced heart injury.…”
Section: Discussionmentioning
confidence: 99%
“…At present, dexrazoxane is the only anthracycline anti-tumor drug cardioprotective agent approved by the FDA (USA), but it is rarely used clinically in China due to its high price and lack of popularity ( 9 , 10 ). Therefore, it is urgent to find a more effective protective drug to protect the heart from the damage of anthracycline anti-tumor drugs.…”
Section: Introductionmentioning
confidence: 99%